Economic Growth in Russia with the Integration of Cross-Border Payments into the Blockchain - M. R. Safiullin; L. A. Elshin; R. T. Burganov (Финансы: теория и практика)
International financial organizations and development institutions agree that the implementation of blockchain technologies (DLT) in the process of cross-border payments will significantly contribute to the development of the global international payment system. In this regard, works devoted to the prospects for the creation of specialized blockchain platforms and international transactions implemented on their basis in the framework of the use of digital currencies are of great interest today. This issue is of particular relevance today for the Russian economy, which is faced with unprecedented sanctions pressure, limiting, in particular, the access of the financial system to international clearing services.   The purpose of this study is to develop and test methodological approaches to the empirical assessment of the potential GDP growth in Russia in the event of simulating the transition of cross-border payments to a blockchain ecosystem.   The research consists of methods for systematizing macroeconomic externalities that are formed in the financial system of the national economy in the process of using blockchain in the system of international settlements, as well as correlation and regression analysis, which provides the opportunity to identify the impact of blockchain transactions on the prospects of economic dynamics. The results of the study consist in the identified potential for a possible increase in Russia’s GDP (+ 4.0 % per year) as part of the use of blockchain in the system for securing international payments. The assessments not only indicate the prospects of using blockchain in the implementation of transnational payments, but also determine the potential for their use in localizing the risks of increasing sanctions pressure, expressed, in particular, in restricting access to international clearing services, payment systems (SWIFT, etc.).